Character Analysis and Service Strategy for Sleeper Bus Consumers on the Malang – Jakarta Route Based on User Perspective - Abiyyu Rahmad Oktantiyo; Hanie Teki Tjendani; Sajiyo (Eduvest - Journal of Universal Studies, 2026)
Sleeper bus services are becoming increasingly inseparable from the long-distance travel experience in Indonesia, especially on the Malang-Jakarta route. This study aims to analyze the characteristics of sleeper bus consumers as well as service strategies that can be applied to meet user expectations. With a survey and interview approach, data is collected from passengers with different demographic backgrounds. The results of the analysis show that the majority of users are private employees with an income above IDR 5,000,000 per month, who use this service for vacations, family visits, and business trips. While sleeper buses offer convenience, there are a number of gaps in terms of cleanliness, punctuality, and responsiveness of service. The study recommends several improvement strategies, including improved cleanliness of facilities, better time management, and interpersonal skills training for bus crews. By implementing this strategy, bus companies are expected to improve customer satisfaction and strengthen their position in the transportation market.